The Influence Of Organizational Climate And Work Environment On Employee Performance With Work Quality As An Intervening Variable At Bank Indonesia Pematangsiantar Representative Office - Handoko Utama; Mesra B (Yayasan Multidimensi Kreatif, 2024)
Humanity holds a very important position in any organization because humans play an important role in the activities of daily life, especially in the workplace environment. Human beings are seen by God as the purest form of life because they have a personality that is different from other forms of life. Without human resources, a business cannot carry out its activities, so human resources are very important. The results of this study are as follows: Organizational Climate has a positive effect of not significant with the original sample value of 0.026 and p values of 0.421. Organizational Climate had a positive and significant effect on Work Quality with the original sample of 0.777 and p values of 0.000. Work Quality had a positive and significant effect on Employee Performance with the original sample of 0.595 and p values of 0.000. The Work Environment had a positive and significant effect on Employee Performance with the original sample value of 0.354 and p values of 0.020. The Work Environment had a positive and insignificant effect on Work Quality with the original sample value of 0.146 and p values of 0.242. Organizational Climate has a positive and significant effect on Employee Performance through Work Quality indirectly with the original sample value of 0.462 and p values of 0.004. The Work Environment has a positive and insignificant effect on Employee Performance through Work Quality indirectly with the original sample value of 0.087 and p values of 0.242.